Customer Knowledge Management (CKM): Model Proposal and Evaluation in a Large Brazilian Higher Education Private Group - Alessandro Henrique de Souza Miake; Rodrigo Baroni de Carvalho; Marcelo de Rezende Pinto; Alexandre Reis Graeml (BBR: Brazilian Business Review)
The CRM process is supported by the relationship orientation and the customer knowledge management derived from data collection, data consolidation, data analysis and knowledge distribution to support decision making. The interaction between CRM and Knowledge Management (KM) is quite intuitive, especially when both are supported by Information Technology. The goal of this paper is to develop a Customer Knowledge Management (CKM) theoretical model in order to assess its contribution to the relationship management of students at one of the largest higher education private groups of the world. A state of contrasts comparing groups of students exposed to CKM-designed marketing campaigns (approximately 600,000 students) and unexposed ones (approximately 17,000 (students) demonstrated how the proposed model effectively contributed to CRM initiatives. It was found that students exposed to marketing activities had a higher reenrollment rate than those that were not reached by the campaign. It was also possible to calculate the return on investment (ROI) of CKM activities.